Structural Development of Health Resort Staff in the Republic of Crimea - Tsekhla, Svetlana Yuryevna; Simchenko, Nataliya Aleksandrovna; Polishchuk, Elena Anatolyevna (Economy of Regions, 2015)
The subject matter of the research is the laws and mechanisms of development of employment in various sectors of the labor market of the Republic of Crimea. The article investigates the regional staffing structure in the development of economic activities of the Republic of Crimea, in particular, the health resort institution to identify priorities for the implementation of employment policies in the region. The main hypothesis of the study: a mismatch of basic parameters of transformation of the labor market in the Republic of Crimea and the educational system produces dysfunctionality of their interaction, causes conflict between the needs and requirements of the labor market and the training level, particularly in the health resort institution, as well as dysfunctionality of formal qualifications of graduates. The methodological basis of the research is a systematic approach to the study of the labor market in the Republic of Crimea and the utilization of statistical methods for analyzing the labor market. In the study, the dynamics of socio-economic development of the Crimean region was analyzed. The labor market conditions in the Crimean region were investigated, which revealed the main causes of imbalances in the labor market development. The analysis of the training of medical students in institutions of higher education was held. Groups of factors affecting the staffing structure in the region were determined. Analysis of the causes of the labor market imbalances in Crimea showed that the existing imbalance was caused by both objective and subjective reasons. Priority lines in employment policy in the health resort institution have been proposed. Their implementation will help to stabilize the situation with the medical staff, including the health resort institution; to improve human resources personnel, capable to provide a high level of service to recreants; to promote problem solving in the development of the Republic of Crimea in the new economic conditions.